TEACHER’S WILLINGNESS TOWARDS THE IMPLEMENTATION OF SCIENTIFIC APPROACH: FROM THEORY TO IMPLEMENTATION - Yogi Surya Syahputra; Riyadi Santosa; Slamet Supriyadi (Journal of English Education, 2017)
Attitude is essential issue to be considered in designing an appropriate learning for learners because it greatly affects the performance and implementation of the teaching and learning process in the classroom. One of the most important attitudes to be explored is the willingness of teachers to implement the curriculum set by the government. This study aims to determine the willingness of English teachers to carry out scientific approach and also to know the implementation of scientific approach in the learning. This research applies qualitative approach with case study design. It is conducted in SMAN 1 Situbondo with three teachers become the informants. Interview and observation are implemented to explore the willingness and the implementation of Scientific Approach. Data analysis in this research using Spradley’s method. From this research, it can be seen that the teachers has enough willingness to apply scientific approach totally. Furthermore, the implementation of scientific approach has been implemented well enough and has implemented it in accordance with government regulation.